Resonant d-wave interaction induced quantum droplet in dipolar atoms. (14th September 2018) - Zhang, Ren
Abstract: Motivated by recent experimental advances on dipolar atoms, we study the Bose gas with anisotropic short-range interaction theoretically. Starting with an anisotropic square well potential, we demonstrate that near the zero-crossing of the s -wave scattering length, there always exists a d -wave resonance. We find that the inter-channel scattering can be characterized by a scattering length. To explore the many-body effect of the short-range anisotropic inter-particle potential, we construct a pseudo-potential which captures the low-energy physics of the raw potential properly. By means of the pseudo-potential, we find the resonant d -wave interaction can inhibit the collapse of the Bose gas induced by the s -wave and dipole–dipole interaction, leading to the formation of the quantum droplet.